Perbedaan Antara Tingkat Kepuasan Pasien Layanan Kefarmasian di Puskesmas Induk Natar dan Puskesmas Rajabasa Indah - Lani Hartanti; Rasmi Zakiah Oktarlina; Zulpakor Oktoba; Asep Sukohar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Background: Pharmaceutical services at primary health centers (puskesmas) play a vital role in supporting the quality of primary healthcare services. However, patient satisfaction with these services varies, influenced by factors such as service quality and demographic characteristics of the patients. In Lampung Province, the Induk Natar and Rajabasa Indah primary health care centers have different regional characteristics, which may influence patients perceptions and satisfaction with pharmaceutical services. Methods: This study employed an analytical observational method with a cross-sectional design. Samples were selected using systematic accidental sampling, with 100 respondents from each primary health care centers. Quantitative data were collected using the Servqual questionnaire and patient sociodemographic characteristics. Data were analyzed using the Mann-Whitney test and the Chi-Square test. Result: The reliability dimension showed the highest satisfaction level in both Induk Natar primary health care centers (90.10%) and Rajabasa Indah primary health care centers (94.05%). Conversely, the tangible dimension had the lowest satisfaction levels, with 88.60% in Induk Natar primary health care centers and 92.08% in Rajabasa Indah primary health care centers. A significant difference in patient satisfaction levels was found between the two health centers. However, no significant correlation was found between patient characteristics (age, gender, education, and occupation) and satisfaction levels (p-value > 0.05). Conclusion: Rajabasa Indah primary health care centers demonstrated a higher level of patient satisfaction compared to Induk Natar primary health care centers. A significant difference in satisfaction levels between the two centers was confirmed by the Mann-Whitney test.